KETAHANAN KELUARGA DI MASA PANDEMI COVID-19 DALAM UPAYA MENCEGAH PERCERAIAN DI KABUPATEN KARAWANG - Tiya Marlina Mufarihah; Rachmat Ramdani; Dadan Kurniansyah (REFORMASI, 2022)
This study aims to describe how family resilience is during the Covid-19 pandemic in an effort to prevent divorce in Karawang Regency. This study used a qualitative descriptive research design. The data collection process was carried out by observation, interviews, documentation, and triangulation accompanied by literature study. The results showed that during the Covid-19 pandemic, family resilience was disrupted and there was a decline, all dimensions of family resilience decreased. Among them are: (1) Physical Resilience, due to layoffs that befell husbands and various household needs that cannot be fulfilled, the community experiences a decrease in the level of physical resilience. (2) Social Resilience, due to layoffs, all indicators in this dimension are not met, so divorce is the last solution. (3) Psychological Resilience, during the Covid-19 pandemic, people experienced psychological resilience disorders where layoffs made housewives experience stress and emotions so that one member left the house and no longer lived together. So it is natural that during the Covid-19 pandemic there was a divorce because the elements of family resilience could not be fulfilled, this is in accordance with the concept of family resilience Dyah Retna Puspita in (Tobirin and Soedirman 2020) that if one of these elements does not work, the level of family resilience disrupted which eventually decreases.